Existence of multiple positive solutions for a third-order boundary value problem with nonlocal conditions - Smirnov, Sergey (Nonlinear Analysis: Modelling and Control, 2023)
We study the existence of multiple positive solutions for a nonlinear third-order differential equation subject to various nonlocal boundary conditions. The boundary conditions that we study contain Stieltjes integral and include the special cases of m-point conditions and integral conditions. The main tool in the proof of our result is Krasnosel’skii’s fixed point theorem. To illustrate the applicability of the obtained results, we consider examples.